Integrating palliative care and heart failure: a protocol for a realist synthesis (PalliatHeartSynthesis). Issue 1 (7th January 2022) - McConnell, Tracey; Burden, John; Duddy, Claire; Hill, Loreena; Howie, Clare; Jones, Bob; Ruane, Bob; Wong, Geoff; Reid, Joanne
Abstract : Introduction: Heart failure affects over 26 million people worldwide with prevalence expected to grow due to an ageing global population. Palliative care can address the holistic needs of patients with heart failure, and integrated palliative care in heart failure management has been indicated to improve outcomes for patients. Despite known benefits for integrated palliative care in heart failure management, implementation is poor across the majority of global health services. Recent systematic reviews have identified the benefits of integrating palliative care into heart failure management and highlighted barriers to implementation. However, there was heterogeneity in terms of countries, healthcare settings, delivery by differing staff across multidisciplinary teams, modes of delivery and different intervention components. Methods and analysis: The aim of this study is to identify how integrated palliative care and heart failure interventions produce desired outcomes, in which contexts, and for which patients. We will undertake a realist synthesis to identify this, using Pawson's five iterative steps. We will recruit an international stakeholder group comprised of healthcare providers and patients with heart failure to advise and provide feedback throughout the review. Our initial realist programme theory sets out the necessary steps needed to accomplish the final intended outcome(s) from the implementation of integrated palliative care and heart failure. This initial programme theory will be shaped through an iterative process of testing and refinement. Ethics and dissemination: Ethical approval is not required for this study. With our stakeholder group, we will coproduce a user guide that outlines practical advice to optimise, tailor and implement interventions designed to integrate palliative care and heart failure, taking into consideration local context, alongside user-friendly summaries of the synthesis findings using short animations to convey complex findings. We will draw on the expertise within the stakeholder group to identify key stakeholders for disseminating to relevant audiences, ensuring outputs are tailored for their respective needs. PROSPERO registration number: CRD42021240185.